2019
DOI: 10.1029/2018tc005462
|View full text |Cite
|
Sign up to set email alerts
|

A Global Plate Model Including Lithospheric Deformation Along Major Rifts and Orogens Since the Triassic

Abstract: Global deep‐time plate motion models have traditionally followed a classical rigid plate approach, even though plate deformation is known to be significant. Here we present a global Mesozoic–Cenozoic deforming plate motion model that captures the progressive extension of all continental margins since the initiation of rifting within Pangea at ~240 Ma. The model also includes major failed continental rifts and compressional deformation along collision zones. The outlines and timing of regional deformation episo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
450
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 406 publications
(525 citation statements)
references
References 102 publications
23
450
0
Order By: Relevance
“…Note that a combination of two letters indicates a distribution in both areas. The left panel shows the positions of continents from the time of nephilid origin until the present day, following Muller et al (2019). Clade numbers match those in Table 2 and in the text [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Methodsmentioning
confidence: 99%
“…Note that a combination of two letters indicates a distribution in both areas. The left panel shows the positions of continents from the time of nephilid origin until the present day, following Muller et al (2019). Clade numbers match those in Table 2 and in the text [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Methodsmentioning
confidence: 99%
“…The arrows in (a) show the motion direction of the Pacific plate with respect to the North American plate (NUVEL‐1A; DeMets et al, ), and the numbers beside the arrows denote the rates of plate motions (mm/year). The seafloor age is from Müller et al (), whose scale is shown atop (a). The thin blue dashed lines in (a) denote depth contours of the subducting Pacific slab (Gou, Zhao, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Bathymetric data were processed and gridded using MB-System tools (Caress & Chayes, 1995) in conjunction with the Generic Mapping Tools (Wessel et al, 2013). Additional bathymetric data in the study region were obtained through the National Oceanic and Atmospheric Administration National Centers for Environmental Information Bathymetric Data Viewer (Müller et al, 2019) slightly modified and shaded by predicted bathymetry (Sandwell et al, 2014), with M series (Nakanishi et al, 1992) and younger (Cande et al, 1989) isochrons. Dashed black line represents Tongereva triple junction trace (Viso et al, 2005).…”
Section: Survey Km1609mentioning
confidence: 99%